2009
DOI: 10.1158/1055-9965.epi-08-0631
|View full text |Cite
|
Sign up to set email alerts
|

Texture Features from Mammographic Images and Risk of Breast Cancer

Abstract: Mammographic percent density (PD) is a strong risk factor for breast cancer, but there has been relatively little systematic evaluation of other features in mammographic images that might additionally predict breast cancer risk. We evaluated the association of a large number of image texture features with risk of breast cancer using a clinic-based case-control study of digitized film mammograms, all with screening mammograms before breast cancer diagnosis. The sample was split into training (123 cases and 258 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
138
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(156 citation statements)
references
References 34 publications
(47 reference statements)
15
138
1
2
Order By: Relevance
“…[3][4][5] Starting with the pioneering work of Wolfe,6,7 studies have long suggested a relationship between mammographic parenchymal patterns and breast cancer risk. [8][9][10][11] These parenchymal patterns are formed by the distribution of fatty, fibroglandular, and stromal breast tissues. An increasingly supported hypothesis is that inherent biological factors, such as endogenous hormonal exposure and genetic predisposition that are associated with the risk of breast cancer, are expressed in a woman's parenchymal tissue and subsequently manifested in her mammographic parenchymal patterns.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Starting with the pioneering work of Wolfe,6,7 studies have long suggested a relationship between mammographic parenchymal patterns and breast cancer risk. [8][9][10][11] These parenchymal patterns are formed by the distribution of fatty, fibroglandular, and stromal breast tissues. An increasingly supported hypothesis is that inherent biological factors, such as endogenous hormonal exposure and genetic predisposition that are associated with the risk of breast cancer, are expressed in a woman's parenchymal tissue and subsequently manifested in her mammographic parenchymal patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Manduca et al performed texture analysis on a case-control study on screen-film mammograms. The texture features showed a similar predicting power for breast cancer risk assessment (area under curve(AUC)00.58-0.60) as that obtained with just breast percent density (AUC00.58) [14]. Wei et al also performed a case-control study with computer-extracted texture features on screen-film mammograms; the AUC of 0.74 was obtained by using combined texture features as the decision variable for differentiating case subjects from control subjects in their study [15].…”
Section: Introductionmentioning
confidence: 67%
“…Also, improvements in contrast normalization should be addressed to avoid underestimating MD in low contrast images. Finally, other parameters could be explored that take into account not only the relative density but also the shape and the distribution of FGT in the breast [20,22] or texture features from the mammogram [21].…”
Section: Discussionmentioning
confidence: 99%